U-shaped association of serum uric acid with all-cause mortality in patients with hyperlipidemia in the United States: a cohort study - Lihua Huang; Zhanpeng Lu; Xiaoyan You; Chunsheng Zou; Liuliu He; Jingxiang Xie; Xiaoqing Zhou (Frontiers in Cardiovascular Medicine, 2023)
BackgroundSerum uric acid (SUA) interferes with lipid metabolism and is considered an independent risk factor for atherosclerosis, a major complication in patients with hyperlipidemia. However, the effects of uric acid levels on mortality in hyperlipidemic patients has yet to be sufficiently determined. In this study, we aimed to assess the association between all-cause mortality and SUA in a hyperlipidemic population.MethodsTo determine mortality rates, we obtained data for 20,038 hyperlipidemia patients from the U.S. National Health and Nutrition Examination Surveys (NHANES) 2001–2018 and National Death Index. To examine the all-cause mortality effect of SUA, multivariable Cox regression models, restricted cubic spline models, and two pairwise Cox regression models were used.ResultsOver a median follow-up of 9.4 years, a total of 2079 deaths occurred. Mortality was examined according to SUA level quintiles: <4.2, 4.3–4.9, 5.0–5.7, 5.8–6.5, and >6.6 mg/dl. In multivariable analysis using 5.8–6.5 mg/dl SUA as a reference, the hazard ratios (95% confidence interval) of all-cause mortality across the five groups were 1.24 (1.06–1.45), 1.19 (1.03–1.38), 1.07 (0.94–1.23), 1.00 (reference), and 1.29 (1.13–1.48), respectively. According to a restricted cubic spline, we noted a U-shaped relationship between SUA and all-cause mortality. The inflection point was approximately 6.30 mg/dl, with hazard ratios of 0.91 (0.85–0.97) and 1.22 (1.10–1.35) to the left and right of the inflection point, respectively. In both sexes, SUA was characterized by a U-shaped association, with inflection points at 6.5 and 6.0 mg/dl for males and females, respectively.ConclusionUsing nationally representative NHANES data, we identified a U-shaped association between SUA and all-cause mortality in participants with hyperlipidemia.